2019
DOI: 10.1039/c9ra04702f
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic efficacy of supported tetrazine on MgZnO nanoparticles for the heterogeneous photodegradation of methylene blue and ciprofloxacin

Abstract: MgZnO@SiO2-tetrazine nanoparticle was synthesized and its photocatalytic efficiency was demonstrated in the decomposition of methylene blue (MB) and ciprofloxacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…The primary reason for the result obtained was the limited production of active radicals, which were insufficient to degrade the higher concentration of MB dye 34 . Also, highly concentrated MB dye solution could decrease the penetration of photons in the solution phase and thus hampered with the photogeneration of electron-hole pairs 35 . It was observed that with the increase in the H 2 O 2 concentration, the MB degradation efficiency decreased by ~3-5% for all the photocatalysts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The primary reason for the result obtained was the limited production of active radicals, which were insufficient to degrade the higher concentration of MB dye 34 . Also, highly concentrated MB dye solution could decrease the penetration of photons in the solution phase and thus hampered with the photogeneration of electron-hole pairs 35 . It was observed that with the increase in the H 2 O 2 concentration, the MB degradation efficiency decreased by ~3-5% for all the photocatalysts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another reason for reduced degradation efficiency might be described by the Beer–Lambert law, according to which, with increase in the dye concentration, a decrease in the path length of photons entering solution was observed, which reduces the degradation efficiency. 83 , 84 Since the maximum efficiency is observed with 15 mg/L therefore, this concentration was taken as the optimized concentration for the remaining reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Various techniques, such as metal/non-metal doping, heterojunction and hybrid composite formation, and so on, have been used to mitigate the aforementioned disadvantages. For example, Parvizi et al [18] synthesized and tested MgZnO@-SiO 2 nanoparticles for the photocatalytic degradation of ciprofloxacin and methylene blue. The scientists claim that immobilizing tetrazine onto MgZnO@SiO 2 À Cl resulted in a photocatalyst with improved performance that degraded 95 % of the methylene blue dye after 20 min under optimal conditions.…”
Section: Introductionmentioning
confidence: 99%